Atypical Presentation of Autoimmune Pancreatitis - Shrestha, Ramila; Shrestha, Milan; Bhusal, Yuvraj; Shrestha, Swarup; Yadav, Ajay Kumar; Khadka, Dibas (Nepal Medical College Journal, 2025)
Autoimmune pancreatitis (AIP) is an inflammation in the pancreas from an autoimmune etiology. It is often difficult to diagnosis with significant morbidity and mortality. It can present with two subtypes of AIP type 1 and type 2. There is limited data on the treatment of autoimmune pancreatitis. Most patients are respond to corticosteroid therapy.